Microcell-mediated chromosome transfer between non-identical human iPSCs - Narumi Uno; Hitomaru Miyamoto; Kyotaro Yamazaki; Masaya Egawa; Hiroaki Kobayashi; Kanako Kazuki; Mitsuhiko Osaki; Teruhiko Suzuki; Shusei Hamamichi; Mitsuo Oshimura; Kazuma Tomizuka; Yasuhiro Kazuki (Elsevier, 2024)
Microcell-mediated chromosome transfer (MMCT) is anticipated as a unique strategy to manipulate numbers of chromosomes, including the generation of hyperaneuploidy syndrome models with human induced pluripotent stem cells (hiPSCs). Mouse A9/Chinese hamster ovary (CHO) cell libraries of human monochromosomal hybrids as chromosome donor cells frequently exhibit chromosomal rearrangement in the components. The generation of a new A9/CHO library is time-consuming and laborious. Here, we developed an MMCT method using hiPSCs as chromosome donor and recipient cells, through micronucleation using paclitaxel and reversine. Membrane fusion during the MMCT was mediated through interactions between the ecotropic viral envelope transiently expressed in chromosome donor cells and mCAT-1 in chromosome recipient cells. This approach involved tagging Chr21 and ChrY by CRISPR-Cas9 and transferring human/mouse artificial chromosomes, Chr21, ChrX, and ChrY, wherein there are no previous reports demonstrating a full-length introduction. Thus, a strategy that combing CRISPR-Cas9-mediated chromosome tagging and MMCT from hiPSCs as chromosome donor cells to hiPSCs as recipient cells systematically produced isogenic disease model hiPSCs with hyperaneuploidy. This approach allows the study of rare diseases and promises to provide new insights into early developmental mechanisms by introducing a comprehensive set of influential chromosomes/regions into hiPSCs.